The impact of induction therapy with three doses of infliximab on deep histological healing in paediatric patients with active Crohn’s disease - Szymanska, Edyta; Dadalski, Maciej; Szymanska, Sylwia; Grajkowska, Wieslawa; Pronicki, Maciej; Kierkus, Jaroslaw (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction: The clinical efficacy of infliximab (IFX) for induction of remission in both adults and children with active Crohn’s disease (CD) has been well documented. Recently, so-called “deep remission” defined as mucosal healing has become the ultimate endpoint of the most recent therapeutic advances for CD. However, endoscopic evidence of mucosal healing is not necessarily associated with histological evidence of suppression of inflammation. Aim: Since data on that issue are limited, especially in the paediatric population, the aim of this study was to assess the impact of induction therapy with IFX on deep microscopic remission in paediatric patients with CD. Material and methods: Fifty-six children (32 boys and 24 girls) aged 13.0 ±9.3 years with moderate to severely active CD diagnosed at the mean age of 5.5 ±0.83 years were included into the study. Colonoscopy and gastroscopy with sample collection were performed in all patients before and after three injections of IFX. Clinical activity of the disease was assessed using the Paediatric Crohn’s Disease Activity Index (PCDAI), and the endoscopic activity was scored using the Simple Endoscopic Score (SES-CD). Histological changes were evaluated by a previously described numerical scoring system. Results: Thirty-nine (69.6%) patients reached clinical remission (PCDAI ≤ 10). When comparing data at baseline and at week 10, a significant decrease was observed in median PCDAI, and in SES-CD score between the initial and control colonoscopies. We also reported a decrease in histological scale. However, the difference was not statistically significant (p = 0.63). Three (5.4%) patients had a score of zero in the control histological examination. The correlation was found only between histological score and SES-CD score. Clinical remission correlated better with mucosal healing expressed by a decrease in SES-CD score than with microscopic changes. Conclusions : Biological therapy with infliximab enables mucosal healing in paediatric patients with CD, which is not necessarily associated with histological evidence of suppression of inflammation. Mucosal healing correlates better than microscopic healing with clinical remission.